EVALUATING RISK FACTORS, CLINICAL AND THERAPEUTIC PROFILE OF STROKE PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL - P, LAKSHMI; S, SUCHITHA; V, SAI ASWANI; SREE V, DHANYA; SK, ZAFEER (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: According to the World Health Organization, stroke is the second leading cause of death for people above the age of 60 years, and the fifth leading cause in people aged 15–59 years old. This study mainly aims to evaluate the prevalence of risk factors, clinical features, pattern of drugs prescribed, and severity of stroke among patients. Methods: A cross-sectional study was carried out in a tertiary care teaching hospital on 210 patients for a period of 6 months. Patients aged 18 years and above were included in the study. The severity of stroke was assessed using National Institute of Health Stroke Scale (NIHSS). Results: The majority of the patients were under the age group of 61–70 years (31%). The incidence of ischemic stroke (81%) was more common compared to hemorrhagic stroke (19%). Males (66%) are prone to stroke compared to females (34%). The most common risk factor was hyperlipidemia (29%) followed by hypertension (17%). Antihypertensives (28%) were most commonly used drugs followed by antihyperlipidemics (23%). Most of the prescriptions were prescribed with 4–6 drugs per prescription (62%). Moderate stroke (69%) was most commonly observed in patients. A total of 147 drug-drug interactions were observed. Among 147 drug-drug interaction, the most commonly observed drug-drug interaction was aspirin with metformin (15%). Conclusion: The present study emphasizes on the need to identify risk factors and providing awareness among the patients by a pharmacist in minimizing the disease burden. Early identification of risk factors and pattern of therapy based on therapeutic guidelines plays a crucial role in qualitative patient care.